A project evaluation and critique on the management of the installation of an access control system - Buenaventura, Adam J. (University of the Philippines Diliman, 2009)
St. Paul University of Manila contracted Unlimited Solutions (Solution Company) to install an Access Control System. The system will be used to monitor and automatically log students and faculties entering and exiting the school premises. The whole system includes Contactless Smart IDs to be distributed to students and faculties. Contactless Smart Card ID readers located at the entrance and exit areas where the IDs will be tapped before entering and exiting school premises. Desktop Computers where the readers are connected and will process the creation of logs and will identify and display through the LCD monitor if the attempt to gain entry is valid or not. A server where all the desktops are connected to centrally process all logs collected from the readers and computers. And lastly, on the software side, an access control and access control manager installed in the computers to process everything. The whole process will be as follows; 1) Contactless Smart Card ID will be enrolled and issued to all enrolled students and faculties, 2) Before entering or accessing the premises, students and faculties will be required to tap issued Smart ID to the readers located at the gate entrance school. 3) Upon exit, students and faculties will be required again to tap the IDs on readers located at the exit gates. 4) Entry and exit logs will be automatically created and stored in the server right after ID was tapped on the reader for monitoring and documenting purposes. 4) All logs are importable from the server for other use-Time and attendance. Project was started last October 1, 2008 and completed last December 28, 2008. There were problems encountered during project implementation which causes a minor slippage on the target completion date. One of the programmers of Unlimited Solutions resigned causing the slippage but was able to cope up with it since the program is almost completed before the resignation and the Head Programmer, as part of his task, is to get involve during the whole process. He was able to pitch-in and completed the needed program.